Dissolved Organic Carbon Loading Stimulates Sediment Phosphorus Mobilization and Release: Preliminary Evidence From Xiangshan Port, East China Sea - Dong, Xu-Meng; Ma, Shuo-Nan; Wang, Hai-Jun; Li, Yuan-Yuan; Li, Yan; Xu, Ji-Lin (Frontiers in Environmental Science, 2022)
Increasing concentrations of dissolved organic carbon (DOC) have been observed in coastal ecosystems worldwide over the past decade, and a tight coupling of the carbon (C) and phosphorus (P) biogeochemical cycle has been recognized in aquatic ecosystems. However, there is still no consensus regarding the potential effects of DOC loading on sediment P release. In a two-month mesocosm experiment, we tested the effects of DOC enrichment on sediment P release in six glass aquariums. Two treatments were set: Control (without C addition) and C addition (equivalent to 5 mg C L-1). The results showed that: 1) DOC loading stimulated coastal sediment P mobilization and release, as indicated by increases in the labile P recorded in-situ for 7 cm deep sediment using diffusive gradients in thin-films and the total P concentrations in the overlying water; 2) stimulated alkaline phosphatase activity, increased P-solubilizing bacteria proportion, and decreased dissolved oxygen concentration were likely the primary mechanisms behind the DOC-stimulated sediment P mobilization and release. These results provide insight into the promotion of sediment P release induced by C-addition. Further studies investigating the quantitative relationships between DOC loadings and P release are needed to fully elucidate the coupled roles of C and P, especially those based on large-scale field investigations with broader C forms and loadings.